Internal finance and growth: microeconometric evidence on Chinese firms - Alessandra Guariglia; Xiaoxuan Liu; Lina Song (Institute for the Study of Labor (IZA), 2008)
Does the availability of internal finance constrain firm growth? Or does it foster it? To answer these questions, we use a panel of 407,096 Chinese firms over the period 2000-2005. We estimate dynamic assets growth equations augmented with cash flow, and find that the growth of state owned enterprises is not affected by cash flow, while that of privately owned firms is most affected. Considering that they represent 62% of the observations in our sample and that, in spite of being typically discriminated against by financial institutions, private firms have experienced sensational growth rates, our results suggest that internal finance has fostered rather than constrained their growth.
urn:nbn:de:101:1-20081126830
Keywords: D92; 330; Assets growth; cash flow; financial constraints; Unternehmensfinanzierung; Selbstfinanzierung; Verschuldungsrestriktion; Unternehmenswachstum; China